PENGARUH KEJELASAN SASARAN ANGGARAN, SISTEM PELAPORAN DAN PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Widya Nisa Wulan Kinasih; Sari Narulita; Zaenuddin Imam (Nusantara Hasana Journal, 2025)
This research aims to analyze the influence of Budget Target Clarity, Reporting System, and Internal Control on the Performance Accountability of Government Agencies (Case Study in the Banyuwangi Regency Local Government). The sample in this study consists of the Regional Secretariat, Regional DPRD Secretariat, Inspectorate, Departments, and Agencies in Banyuwangi Regency, totaling 27 SKPD, using the convenience sampling method. The study involves 54 respondents. Primary data was collected through a questionnaire, and data analysis employed instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and determination coefficient tests using SPSS Version 26. The research findings indicate that budget target clarity does not significantly influence the performance accountability of government agencies, evidenced by a t-value of 1.234 < t-table 2,008 and a significance value (sig) of (0.223 > 0.05) The reporting system does not significantly influences the performance accountability of government agencies, with a t-value of 1.789 < t-table 2,008 and a sig value of (0.080 > 0.05). Internal control significantly influences the performance accountability of government agencies, with a t-value of 2.378 > t-table 2,008 and a sig value of (0.021 < 0.05).